YEATS2 links histone acetylation to tumorigenesis of non-small cell lung cancer. Issue 1 (December 2017) - Mi, Wenyi; Guan, Haipeng; Lyu, Jie; Zhao, Dan; Xi, Yuanxin; Jiang, Shiming; Andrews, Forest; Wang, Xiaolu; Gagea, Mihai; Wen, Hong; Tora, Laszlo; Dent, Sharon; et al.
Abstract Recognition of modified histones by "reader" proteins constitutes a key mechanism regulating diverse chromatin-associated processes important for normal and neoplastic development. We recently identified the YEATS domain as a novel acetyllysine-binding module; however, the functional importance of YEATS domain-containing proteins in human cancer remains largely unknown. Here, we show that theYEATS2 gene is highly amplified in human non-small cell lung cancer (NSCLC) and is required for cancer cell growth and survival. YEATS2 binds to acetylated histone H3 via its YEATS domain. The YEATS2-containing ATAC complex co-localizes with H3K27 acetylation (H3K27ac) on the promoters of actively transcribed genes. Depletion of YEATS2 or disruption of the interaction between its YEATS domain and acetylated histones reduces the ATAC complex-dependent promoter H3K9ac levels and deactivates the expression of essential genes. Taken together, our study identifies YEATS2 as a histone H3K27ac reader that regulates a transcriptional program essential for NSCLC tumorigenesis. Histone modification recognition is an important mechanism for gene expression regulation in cancer. Here, the authors identify YEATS2 as a histone H3K27ac reader, regulating a transcriptional program essential for tumorigenesis in human non-small cell lung cancer.